Dynamical Janus interface design for reversible and fast-charging zinc–iodine battery under extreme operating conditions - Zong, W; Li, J; Zhang, C; Dai, Y; Ouyang, Y; Zhang, L; Li, J; Zhang, W; Chen, R; Dong, H; Gao, X; Zhu, J; et al. (American Chemical Society, 2024)
Aqueous zinc (Zn) iodine (I2) batteries have emerged as viable alternatives to conventional metal-ion batteries. However, undesirable Zn deposition and irreversible iodine conversion during cycling have impeded their progress. To overcome these concerns, we report a dynamical interface design by cation chemistry that improves the reversibility of Zn deposition and four-electron iodine conversion. Due to this design, we demonstrate an excellent Zn-plating/-stripping behavior in Zn||Cu asymmetric cells over 1000 cycles with an average Coulombic efficiency (CE) of 99.95%. Moreover, the Zn||I2 full cells achieve a high-rate capability (217.1 mA h g–1 at 40 A g–1; C rate of 189.5C) at room temperature and enable stable cycling with a CE of more than 99% at −50 °C at a current density of 0.05 A g–1. In situ spectroscopic investigations and simulations reveal that introducing tetraethylammonium cations as ion sieves can dynamically modulate the electrode–electrolyte interface environment, forming the unique water-deficient and chloride ion (Cl–)-rich interface. Such Janus interface accounts for the suppression of side reactions, the prevention of ICl decomposition, and the enrichment of reactants, enhancing the reversibility of Zn-stripping/-plating and four-electron iodine chemistry. This fundamental understanding of the intrinsic interplay between the electrode–electrolyte interface and cations offers a rational standpoint for tuning the reversibility of iodine conversion.